Utilização de caseína fosfato de cálcio amorfo (CPP-ACP) sobre lesões de manchas brancas: ensaio clínico randomizado - Mendes, Ana Carolina Bosco [UNESP] (2015)
The aim of this study was to evaluate the efficacy of CPP-ACP in remineralization of white spot lesions in 80 prior teeth of children aged 5-13 years old enrolled in public schools of the city of Botucatu -SP. The study counted on 36 individuals divided into 4 experimental groups: 1 control (placebo); 2- fluoride gel; CPP -ACP 3; 4- CPP- ACP + fluoride gel. Two applications were performed of such products by a calibrated examiner with a week of interval between these. The monitoring of the lesions was accomplished with the DIAGNOdent Pen Device, before the first application, before the second application, after 1 and 3 months of the first application. In study of the lesion intensity, the Friedman test was applied and for the comparison between experimental groups, Kruskal-Wallis test was applied. The analyses were complemented with the Dunn test and the level of significance was 5%. At the end of the 90-days trial, the use of CPP ACP and fluoride showed improvement in remineralization with statistical similarity in the results. The best result in the white spots lesion remineralization was observed when CPP ACP and fluoride were associated. Authors concluded that the use of the CPP-ACP is a good alternative for the remineralization of white spots lesions and that the effect can be improved when this product is used associated with fluoride.